Synthesis and Antibacterial Efficacy of Nipa Palm Vinegar-Graphene Quantum Dots against Staphylococcus aureus and Escherichia coli - Teppaya, Nongyao; Porrawatkul, Paweena; Rattanaburi, Parintip; Noypha, Amnuay; Kuyyogsuy, Arnannit; Chanthai, Saksit; Nuengmatcha, Prawit (Asian Journal of Chemistry, 2022)
Nipa palm vinegar (NPV) is an essential product from the Pak Phanang district in the Nakhon Si Thammarat Province, Thailand. NPV is used for cooking and its antibacterial activity reduces dependency on toxic chemicals such as antibiotics and preservative foods. Using NPV as the precursor, nipa palm vinegar–graphene quantum dots (NPV-GQDs) were successfully synthesized through pyrolysis. Preliminary screening of the antibacterial activities of NPV and NPV-GQDs against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacterial strains were determined by using the agar well diffusion method. The broth macro-dilution method determined the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The diameter of the inhibition zones of S. aureus and E. coli reached 29.30 mm and 23.50 mm, respectively. The MIC of NPV-GQDs against S. aureus and E. coli was 6.25 mg/mL and 12.50 mg/mL, respectively, whereas the MBC of NPV-GQDs against S. aureus and E. coli was 50.00 mg/mL. These results signify the potential healthcare application of NPV-GQDs as high-quality and valuable antimicrobial agents, thereby reducing chemical usage toxic to the body in the future.